2013
DOI: 10.1182/blood-2013-01-479188
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution in relapsed NPM1-mutated acute myeloid leukemia

Abstract: Key Points• Relapsed AML with NPM1 mutation is genetically related to the primary leukemia and characterized by an increase in high-risk aberrations.• DNMT3A mutations show the highest stability and thus may precede NPM1 mutations.Mutations in the nucleophosmin 1 (NPM1) gene are considered a founder event in the pathogenesis of acute myeloid leukemia (AML). To address the role of clonal evolution in relapsed NPM1-mutated (NPM1 mut ) AML, we applied high-resolution, genome-wide, single-nucleotide polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
225
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(255 citation statements)
references
References 41 publications
16
225
2
2
Order By: Relevance
“…A number of authors have recommended the development of strategies to target and eliminate clonal reservoirs of HSCs containing pre-leukemic mutations. 13,15,16,18 Such strategies must take into account that CH appears to be quite common in elderly asymptomatic individuals and that absolute risks for progression to hematological malignancy are low. On the basis of the observations described here, targeting known pre-leukemic driver mutations may address only a fraction of the at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have recommended the development of strategies to target and eliminate clonal reservoirs of HSCs containing pre-leukemic mutations. 13,15,16,18 Such strategies must take into account that CH appears to be quite common in elderly asymptomatic individuals and that absolute risks for progression to hematological malignancy are low. On the basis of the observations described here, targeting known pre-leukemic driver mutations may address only a fraction of the at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…12 Mutations of these so-called "early genes" can persist in HSCs of patients in remission, creating reservoirs of pre-leukemic clones that can engender a relapse. [13][14][15][16] Early gene mutations are also detectable in mature blood cells of patients with AML and some subjects with skewed X-inactivation, but ostensibly normal hematopoiesis. 13,16,17 The frequencies of the mutant alleles in these cases indicate the mutant cells must have undergone clonal expansions, despite retaining a capacity to differentiate normally.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, we showed that immunophenotypically defined subpopulations of cells prominent at relapse could be traced back as very minor immature (CD34+/CD38−/dim) subpopulations of cells at diagnosis [32], again suggesting the importance of the CD34+/CD38− leukemic stem cell fraction. Since LSC are currently followed during therapy as biomarker of treatment efficacy and as prognostic factor for relapse, it is of great relevance to identify all (possibly minor) LSC populations that are potentially capable of causing relapse [37].…”
Section: Lsc Heterogeneity Of Lsc Within a Patientmentioning
confidence: 99%
“…3 More than 40 mutations have been described, but 75% of cases show the same genetic alteration in exon 12, named NPM1 mutation A. NPM1 mut represent relatively early events in leukemogenesis, and thus can be considered stable markers to be tracked throughout leukemia history and clonal evolution. 4,5 In line with that, numerous studies have demonstrated the usefulness of landmark analyses and longitudinal monitoring of NPM1 mut in AML patients after chemotherapy. 6,7 However, information on the clinical utility of NPM1 mut quantitative monitoring in the post-transplantation setting are to date more limited, [7][8][9] and thus represent the specific focus of our present study.…”
mentioning
confidence: 67%
“…It should however be emphasized that NPM1 mut is present in only a subset of AML patients, and in even fewer of those who receive allogeneic HSCT. Moreover, even though generally stable over the disease course, NPM1 mut can be lost during clonal evolution, 4 as occurred also in one of the cases included in our analysis. In this view, the evaluation of earlier events in leukemogenesis, such as mutations in DNMT3A or IDH1/2, appears worthy of future investigation: although these preleukemic mutations have been shown to persist after chemotherapy even in patients who will not relapse, 14,15 in allogeneic HSCT the persistence of host hematopoiesis, especially if of clonal origin, would bring no benefit whatsoever, and might be more easily and safely targeted by 'soft' therapeutic measures such as tapering of immunosuppressants.…”
mentioning
confidence: 82%